Active learning in scientific writing skill using Indonesian textbook based on character education. (December 2019) - Slamet, St. Y.; Winarni, R; Hartono,
Abstract: The purpose of this study was to describe development of text-based and character-based Indonesian textbook model. The method was research and development which consists of four stages, they are: (1) Exploration, (2) Model Development, (3) Model Testing, and (4) Disemination. The research approach in the exploration stage was qualitative descriptive approach. Data collection was done through in-depth interviews, observation, documentation, and questionnaires. Data analysis technique was done by interactive analysis model. Experimental research was done in the model testing stage. The results of this study: (1) exploration stage showed that the Indonesian textbooks used in UNS, UMS, and UNISRI Surakarta, have not been in accordance with the needs of students and lecturers, (2) model development stage produced a character-based scientific writing textbook through preliminary field testing; and (3) the effectiveness testing showed that the value of t obtained was 0.17 which then compared with the value of t table (with N = 90, α = 0.05) pointing 1.64. Thus, the t-obtained (0.17) > t-table (1.64), the hypothesis was accepted (Ho was rejected) and the textbook was stated significant. This means that the text-based and character-based Indonesian textbook was effective to improve scientific writing skills.